The implementation of creating shared value in Indonesian companies - Usman, Syarif; Sulastri; Yuliani (Technium Social Sciences Journal, 2024)
Social responsibility has become a corporate obligation, which is carried out in the form of programs that participate in the welfare of the community, as well as activities that are concern for the environment. After a long time, these programs and activities were carried out, it turned out that the benefits and benefits obtained by the company were not optimal, such as the benefits that would be obtained long-term and indirect economic benefits. The concept of Creating Shared Value is a breakthrough in the implementation of corporate social responsibility, which provides mutual benefits not only to the community and the environment and all stakeholders, but also to the company itself, especially economic benefits. The concept of Creating Shared Value has been adopted and applied to several companies in Indonesia, both private companies and State-Owned Enterprise companies.